Highly breathable, surface-hydrophobic and wet-adhesive silk based epidermal electrode for long-term electrophysiological monitoring. (10th November 2022) - Yan, Xueling; Chen, Song; Zhang, Guangyong; Shi, Wei; Peng, Zefei; Liu, Zelin; Chen, Yizhong; Huang, Yonghui; Liu, Lan
Abstract: Epidermal electrodes for long-term electrophysiological signals monitoring have great potentials in bioelectronics such as health monitoring, disease diagnosis, and human-machine interaction. However, it still remains challenges for epidermal electrodes with simultaneously high breathability, surface self-cleaning, and robust skin-adhesion, which may cause skin discomfort, loosing adhesion, and misleading signals during long-term using. In this work, based on the soft and wet-adhesive silk fibroin nanofibers membrane, we report a novel three-layer all-nanofiber-based polytetrafluoroethylene (PTFE)/silver nanowires (Ag NWs)/silk fibroin nanofibers membrane (Silk NFs) fabric electrode. This hierarchical porous structure endows the fabric with thinness (∼10 μm), high conductivity (∼3.58 Ω/sq), high breathability (51.5 mm/s, water vapor transmission rate (WVTR) = 2553 g m −2  d −1  at 35 °C), wet skin-adhesion (13 N/m on wet skin), and surface hydrophobicity (contact angle of 142.3°). As a result, it can be conformally attached to the skin with no skin irritation and prevent sweat accumulation and immersion. Furthermore, compared to the commercial Ag/AgCl gel electrodes, the as-prepared fabric electrode in this work provides a better skin-electrode interface, so that the obtained electrochemical signals in exercise have higher signal qualities with equivalent signal strength and lower signal noise. Therefore, this fabric electrode may further promote the development of epidermal electrode in real-time long-term use. Graphical abstract: Image 1